Optimization extraction and bioactivities of polysaccharide from wild Russula griseocarnosa - Ye Yuan; Yang Liu; Mengdi Liu; Qian Chen; Yuanyuan Jiao; Yan Liu; Zhaoli Meng (Elsevier, 2017)
The extraction conditions and biological activities of polysaccharides from wild Russula griseocarnosa (PRG) were investigated. Response Surface Methodology (RSM) with a Box-Behnken Design (BBD) was used to optimize extraction conditions. The optimal extraction parameters of PRG were as follows: extracting time 4 h, extraction temperature 77.3 °C and liquid-solid ratio 42.5 g/L. Furthermore, the data demonstrated that PRG exhibited antioxidant activities evidenced by reducing power to scavenge the DPPH, ABTS, hydroxyl radical and superoxide radical. PRG showed the activity of anti-cervical carcinoma cells Hela and Siha. In conclusion this study offered an efficient extraction method of wild Russula griseocarnosa polysaccharide, and the results suggested PRG had good antioxidant and inhibitory activities against cervical carcinoma cells, and PRG could be developed as a novel natural functional food. Keywords: Russula griseocarnosa, Response surface methodology, Polysaccharide, Antioxidant activity, Anti-tumor activity